Research on real time measurement model and measurement system for gas concentration in extraction drilling - Dayang Yu; Junhao Zhu; Xing Li; An He; Huaiqian Liu; Changjiang Chen; Yong Liu (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract Accurate and real-time monitoring of methane concentration at extraction boreholes is critical for intelligent gas management in coal seams. Although tunable diode laser absorption spectroscopy (TDLAS) offers high sensitivity and rapid response, its performance is limited under complex underground conditions due to low signal-to-noise ratios and lack of effective environmental compensation, leading to reduced detection accuracy at low concentrations. This study develops an enhanced TDLAS-based detection system that integrates wavelength modulation spectroscopy (WMS) with a centroid-weighted Lagrange interpolation algorithm. The system accounts for fluctuations in borehole gas composition, pressure, and temperature, enabling dynamic compensation for spectral distortion and improved measurement reliability. Experimental validation using 0.5% and 4.5% CH₄ standard gases yielded the following key findings:(1) Methane concentration accuracy is highly dependent on line strength and spectral shape, both sensitive to temperature and pressure. (2) The Lorentzian profile was selected as the optimal line shape for pressure-broadened conditions, and the proposed interpolation algorithm effectively compensates for dual-variable spectral shifts. (3) The system achieves a maximum measurement error below 0.5%, demonstrating strong robustness and precision in variable environments. This work provides a compact, accurate, and environment-adaptive solution for methane monitoring at borehole outlets and supports the development of intelligent gas sensing systems in coal mining applications.